Ferroelectric polymer-based all-organic composite material for photo-thermal and photoelectric conversion, preparation method and application
By blending ultra-small polyschiff alkali nanoparticles with ferroelectric polyvinylidene fluoride polymers, composite materials can achieve strong photothermal and high photoelectric conversion in the ultraviolet-visible-near infrared range, solving the problems of poor dispersion of existing materials in organic solvents and insufficient ability to convert visible light in organic solvents, and achieving efficient photoelectric conversion and photoelectric response.
Patent Information
- Application Number
- CN202311416748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-30
AI Technical Summary
The existing conjugated organic polymer photothermal materials are difficult to disperse in organic solvents, which limits their recombination with ferroelectric polymers, and mainly focuses on the energy conversion of near-infrared light. There are few reports on visible light photothermal conversion materials.
Ultra-small polyschiff alkali nanoparticles were prepared and blended with ferroelectric polyvinylidene fluoride polymer. The nanocomposite film was prepared by solution blending and casting to achieve strong light-thermal and photoelectric conversion in the ultraviolet-visible-near-infrared range.
It realizes strong photothermal conversion and high photoelectric voltage in the ultraviolet-visible-near-infrared range, exceeding the performance of traditional semiconductor materials, and has potential applications in fields such as energy conversion and photodetection.
Smart Images

Figure CN119912713A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new functional materials, and mainly relates to a ferroelectric polymer-based all-organic composite material for photothermal and photoelectric conversion, a preparation method and an application. The present invention prepares a new type of ultra-small poly Schiff base nanoparticle that can produce strong photothermal conversion in a wide wavelength range of ultraviolet-visible-near infrared. By combining the nanoparticle with a ferroelectric polymer, a composite material that can produce strong photothermal and photoelectric conversion in a wide wavelength range of ultraviolet-visible-near infrared can be prepared. Background Art
[0002] Photothermal materials are a type of material that can convert absorbed light energy into thermal energy. With the development of optical technology, photothermal conversion materials are increasingly used in the fields of chemical industry, energy, sensing and life health. In recent years, photothermal materials based on conjugated organic polymers have developed rapidly, especially in the fields of energy harvesting and disease diagnosis and treatment. At present, the classic organic photothermal materials include polyaniline, polypyrrole, polythiophene and polydopamine. However, the main conjugated organic polymer photothermal materials are hydrophilic and easy to disperse in aqueous solvents, but relatively cannot be well dispersed in organic solvents. This makes it difficult for such materials to be simply compounded with other functional polymers such as ferroelectric polymers by solution blending, which may limit their application in the fields of organic composite materials. In addition, the main conjugated organic polymer photothermal materials currently focus on the energy conversion of near-infrared light, and there are relatively few reports on materials that can perform visible light photothermal conversion. The development of materials with strong visible light absorption and photothermal conversion capabilities may be beneficial to promote the sensing of visible light and the utilization of energy.
[0003] Poly-SchiffBase (usually translated as Schiff base) polymer materials containing carbon-nitrogen double bond structures usually have a variety of properties such as nonlinear optics, intrinsic conductivity and thermal stability; their optical and electrical properties have become a research hotspot in recent years. There are many types of poly-Schiff base materials, and a wide range of materials can be selected. If a larger photothermal response can be generated in poly-Schiff base materials, the functionality of poly-Schiff base materials can be expanded, and the types of photothermal conversion materials can be enriched.
[0004] Ferroelectric polymers are a typical type of functional polymer materials. Their research and application directions are concentrated in the fields of dielectrics, piezoelectrics, and pyroelectrics. The pyroelectric effect refers to the phenomenon of charge release that occurs when polarization intensity changes with temperature. Macroscopically, the change in temperature causes voltage or current to appear at both ends of the material. Since the photothermal effect can be used to convert light energy into thermal energy, we try to combine ferroelectric polymers with photothermal materials and use the coupling of the photothermal effect and the pyroelectric effect to achieve photoelectric conversion. In traditional semiconductor photoelectric systems, the photoelectric voltage value is usually limited by the band gap of the material. Materials constructed using this photothermal-pyroelectric mechanism are not restricted by the band gap of the material itself and are expected to achieve high photoelectric voltages that far exceed traditional semiconductor photoelectric materials. If this mechanism can be used to produce a larger photoelectric response in ferroelectric polymers, the functionality of ferroelectric materials can be expanded, while enriching the types of photoelectric materials. This type of material has potential applications in photoelectric conversion devices and artificial visual prostheses. Summary of the invention
[0005] The present invention provides a ferroelectric polymer-based all-organic composite material for photothermal and photoelectric conversion, a preparation method and application. The present invention prepares a new type of ultra-small poly Schiff base (poly 4-amino-1-naphthaldehyde) nanoparticles that can produce strong photothermal conversion in a wide wavelength range of ultraviolet-visible-near infrared. Further, we try to simply prepare a nano-composite film by using solution blending and casting methods with this ultra-small conjugated poly Schiff base nanoparticle and a ferroelectric polyvinylidene fluoride (PVDF)-based polymer (such as a copolymer of vinylidene fluoride and trifluoroethylene P (VDF-TrFE)). In the final composite material, the nanoparticles can be evenly dispersed, and the composite material can show a strong photothermal conversion ability in a wide wavelength range of ultraviolet-visible-near infrared. Since ferroelectric polymers have a pyroelectric response, we try to achieve photoelectric conversion by coupling the photothermal effect with the pyroelectric effect. The polarized composite film can produce strong photoelectric conversion in a wide wavelength range of ultraviolet-visible-near infrared, such as at 100mW / cm 2 The 450nm light can produce a temperature change of about 23℃, and achieve an open circuit voltage of 42.4V and an electric charge of 501.5μAm by coupling the photothermal effect with the pyroelectric effect. -2 The short-circuit current density of this composite material is more than 40V, which is significantly higher than the current mainstream semiconductor-based photoelectric voltage (~1V), which may be more conducive to the application of materials in energy conversion and light detection. In addition, there is the possibility of blending poly-4-amino-1-naphthaldehyde nanoparticles with other ferroelectric polymers to construct a composite material with high photoelectric response.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing a ferroelectric polymer-based all-organic composite material for photothermal and photoelectric conversion, comprising the following steps: heating and refluxing the monomer 4-amino-1-naphthaldehyde in a first polar solvent under the protection of an inert gas to dehydrate and condense it to obtain poly-4-amino-1-naphthaldehyde, dissolving the poly-4-amino-1-naphthaldehyde and a ferroelectric PVDF-based polymer in a second polar solvent and casting and drying the solution, and polarizing it under a high voltage electric field to obtain the composite material. The film needs to be in a state where the coercive field of the ferroelectric PVDF-based polymer exceeds 50 MVm -1 ) under an external electric field (polarization time > 1 min).
[0008] In the present invention, the high voltage electric field refers to a field exceeding the coercive field (50MVm -1 For example, the high voltage electric field is greater than 50 MVm -1 And less than or equal to 200MVm -1 The electric field.
[0009] Furthermore, the first polar solvent is ethanol, ethyl acetate, N,N-dimethylformamide or N-methylpyrrolidone; and the second polar solvent is N,N-dimethylformamide or N-methylpyrrolidone.
[0010] Further, based on the total weight of the poly 4-amino-1-naphthaldehyde and the ferroelectric PVDF-based polymer, the content of the poly 4-amino-1-naphthaldehyde is 0 to 40wt%. For example, the content of the poly 4-amino-1-naphthaldehyde is 0, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%. %, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, or 40wt%.
[0011] Further, the temperature of heating and refluxing is 25 to 200° C., and the heating and refluxing time is 12 to 54 hours. The temperature of heating and refluxing is 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 150° C., 160° C., 170° C., 180° C., 190° C. or 200° C., and the heating and refluxing time is 12, 18, 24, 36, 38, 40, 45, 50 or 54 hours.
[0012] The composite material obtained by the method as described in any one of the above, wherein the composite material is a film, and the thickness of the film is 5-200 μm. For example, the thickness of the film is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm, 40μm, 50μm, 60μm, 70μm, 80 μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 170μm, 180μm, 190μm or 200μm.
[0013] Application of the composite material prepared by the method described in any one of the above items or the composite material described above in photothermal and photoelectric conversion.
[0014] Specifically, a method for preparing a ferroelectric polymer-based all-organic composite material for photothermal and photoelectric conversion includes heating and refluxing the monomer 4-amino-1-naphthaldehyde in an ethyl acetate solution under argon protection to dehydrate and condense it, and collecting the precipitate to obtain poly-4-amino-1-naphthaldehyde. Due to its low degree of polymerization and rigid chain structure, this conjugated poly-Schiff base material can spontaneously form ultra-small polymer nanoparticles, and can be stably and uniformly dispersed in polar solvents such as DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone). By dissolving poly-4-amino-1-naphthaldehyde and a ferroelectric PVDF-based polymer in a polar solvent such as DMF or NMP and casting and drying the solution, a composite material with uniformly dispersed poly-Schiff base nanoparticles can be obtained.
[0015] Using ferroelectric PVDF-based polymers with coercive fields exceeding 50 MVm -1 The composite material after electric field polarization can produce strong photothermal and photoelectric conversion in a wide wavelength range of ultraviolet-visible-near infrared, such as 100mWcm -2The 450nm light can produce a temperature change of about 23℃, an open circuit voltage of 42.4V and an -2 In contrast, the photoelectric voltage value of semiconductor photoelectric systems that rely on the photovoltaic effect is usually limited by the band gap of the material, resulting in such materials usually only absorbing light in a specific wavelength range and usually only having a maximum open circuit voltage of about 1V. The composite material we prepared has great advantages in terms of light response wavelength range and open circuit voltage.
[0016] Advantages and positive effects:
[0017] The nanocomposite material for photothermal and photoelectric conversion prepared by blending ultrasmall conjugated poly-Schiff base nanoparticles with photothermal conversion capability with ferroelectric polymers with pyroelectric effect has the following advantages:
[0018] (1) The synthesized new conjugated poly-Schiff base: poly-4-amino-1-naphthaldehyde, can produce strong photothermal conversion in a wide wavelength range of ultraviolet-visible-near infrared. It is also ultra-small in size and easy to disperse. It can be prepared into a composite material with uniformly dispersed nanoparticles by simple solution blending and casting. The preparation method is highly operable and simple in process.
[0019] (2) The composite material has strong absorption in a wide wavelength range of ultraviolet-visible-near infrared, which is beneficial to improve the utilization efficiency of light energy;
[0020] (3) The optoelectronic composite material based on the coupling of photothermal and pyroelectric effects overcomes the voltage limitation of the optoelectronic system based on semiconductor materials and has an open circuit voltage value far exceeding that of other optoelectronic materials reported in the literature. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The invention relates to a method for obtaining poly 4-amino-1-naphthaldehyde by polymerizing monomer 4-amino-1-naphthaldehyde.
[0022] Figure 2 This is an ultrathin section TEM of a composite film of poly (4-amino-1-naphthaldehyde) ultrasmall nanoparticles (2wt% content) and ferroelectric P (VDF-TrFE) copolymer.
[0023] Figure 3 The results of the composite materials with different poly-4-amino-1-naphthaldehyde contents at 100 mWcm -2 Open circuit voltage and short circuit current density curves under 405nm light.
[0024] Figure 4 The composite material with 2wt% poly-4-amino-1-naphthaldehyde content was -2 450nm light can produce a temperature change of about 23℃.
[0025] Figure 5 The composite material with 2wt% poly-4-amino-1-naphthaldehyde content was -2 Open circuit voltage and short circuit current density curves under 405-850nm light. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.
[0027] The composite film material of poly 4-amino-1-naphthaldehyde ultra-small nanoparticles and ferroelectric P (VDF-TrFE) copolymer proposed by the present invention can be simply prepared by a casting method of a mixed solution. This composite material can show strong photothermal and photoelectric conversion capabilities in a wide wavelength range of ultraviolet-visible-near infrared. Here, the feasibility of this method is illustrated by the present invention using poly 4-amino-1-naphthaldehyde (PANA) nanoparticles and P (VDF-TrFE) (7030).
[0028] Example 1: Synthesis of poly 4-amino-1-naphthaldehyde nanoparticles.
[0029] 4-Amino-1-naphthaldehyde (0.58 g, 3.4 mmol) was dissolved in ethyl acetate (25 mL), and triethylamine (0.3 mL, 21 mmol) was added to provide an alkaline environment. The mixed solution was refluxed in argon at 70° C. for 48 hours to obtain a dark brown solid residue, such as Figure 1 The solid residue was washed with ethanol and dried in vacuo to give 0.36 g (yield 62%) of poly(4-amino-1-naphthaldehyde).
[0030] Example 2: Preparation of a composite film of P(VDF-TrFE) copolymer and poly-4-amino-1-naphthaldehyde by a casting method.
[0031] First, poly(4-amino-1-naphthaldehyde) (PANA) and P(VDF-TrFE) (Piezotech, Arkema Group, France) prepared in Example 1 were dissolved in 4 mL DMF and stirred overnight. The uniform mixture was then cast on a clean glass plate and dried in an oven at 80°C for 2 h. After naturally cooling to room temperature, the composite film was peeled off the glass plate and dried in a vacuum oven at 135°C for 5 h to remove residual solvent and improve crystallinity; a composite film (film thickness 20 μm) with uniformly dispersed nanoparticles was obtained. Wherein poly (4-amino-1-naphthaldehyde) (PANA) and P (VDF-TrFE) total 0.2g, based on the total mass of poly (4-amino-1-naphthaldehyde) and P (VDF-TrFE), the content of poly (4-amino-1-naphthaldehyde) is 0wt%, 0.5wt%, 1wt%, 2wt%, 5wt% and 10wt%, respectively, to obtain films with different contents of poly (4-amino-1-naphthaldehyde). Figure 2 As shown, the TEM image of the ultra-thin sectioned composite film (the content of poly(4-amino-1-naphthaldehyde) is 2wt%) after staining with ruthenium tetroxide vapor. The thin film-like substance visible in the image is the P(VDF-TrFE) matrix, and the nanoparticles are PANA nanoparticles.
[0032] Example 3: Photoelectric response of composite films with different poly 4-amino-1-naphthaldehyde contents.
[0033] The composite film obtained in Example 2 was heated at 100 MVm -1 After 5 minutes of polarization under electric field strength, indium tin oxide (ITO) was plated on the composite film. The ITO thickness of 100 nm was used for subsequent photoresponse testing. The composite materials with different nanoparticle contents all had good photoelectric responses, such as Figure 3 shown.
[0034] The composite material has a strong photothermal response in a wide wavelength range. The composite material with 2wt% poly-4-amino-1-naphthaldehyde content has a strong photothermal response at 100mWcm -2 The 450nm light can produce a temperature change of about 23℃, such as Figure 4 As shown in the infrared thermal image, the composite material with 2wt% poly 4-amino-1-naphthaldehyde content is compared with that before illumination (left) at 100mWcm -2 The 450nm light (right) can produce a temperature change of about 23℃. Due to the coupling of the photothermal effect of poly (4-amino-1-naphthaldehyde) nanoparticles and the pyroelectric effect of P(VDF-TrFE) copolymer, the 2wt% poly (4-amino-1-naphthaldehyde) content composite material can generate a temperature change of about 23℃ under 100mW cm -2 It can show high open circuit voltage and short circuit current density under 405-850nm light, such as Figure 5 shown.
[0035] The present invention does not elaborate on some of the common technologies of those skilled in the art. The above-described embodiments are only descriptions of preferred implementations of the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementations described. Without departing from the design spirit of the present invention, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the scope of protection determined by the claims of the present invention.
Claims
1. A method for preparing a ferroelectric polymer-based all-organic composite material for photothermal and photoelectric conversion, characterized in that: The method comprises the following steps: heating and refluxing the monomer 4-amino-1-naphthaldehyde in a first polar solvent under the protection of an inert gas to make it dehydrate and condense to obtain poly 4-amino-1-naphthaldehyde; dissolving the poly 4-amino-1-naphthaldehyde and a ferroelectric PVDF-based polymer in a second polar solvent and casting and drying the solution to obtain the composite material.
2. The method according to claim 1, characterized in that The first polar solvent is ethanol, ethyl acetate, N,N-dimethylformamide, chloroform or N-methylpyrrolidone; the second polar solvent is N,N-dimethylformamide or N-methylpyrrolidone.
3. The method according to claim 1, characterized in that Based on the total weight of the poly-4-amino-1-naphthaldehyde and the ferroelectric PVDF-based polymer, the content of the poly-4-amino-1-naphthaldehyde is 0-40wt%.
4. The method according to claim 1, characterized in that: The heating reflux temperature is 25 to 200° C., and the heating reflux time is 12 to 54 hours.
5. The composite material obtained by the method according to any one of claims 1 to 4, characterized in that: The composite material is a film, and the thickness of the film is 5-200 μm.
6. The composite material according to claim 5, characterized in that The film needs to be polarized (polarization time>1 min) under an external electric field exceeding the coercive field (>50 MV / m) of the ferroelectric PVDF-based polymer.
7. Use of the composite material obtained by the method according to any one of claims 1 to 4 or the composite material according to claim 5 in photothermal and photoelectric conversion.
Citation Information
Patent Citations
Electrocatalyst for sulfur-nitrogen-transition metal co-doped carbon-based oxygen reduction, and preparation method and application thereof
CN109473684A
Schiff base polymer / carbon nanotube composite electrode material with shish-kebab structure and preparation method of Schiff base polymer / carbon nanotube composite electrode material
CN110148720A
Benzo-pyronine near-infrared fluorescent dye as well as preparation method and application thereof
CN111793052A
Method for fixing and removing temporary shape by ferroelectric polymer and application
CN114369270A
Glucagon antagonists / inverse agonists
US6613942B1